In vitro-derived leukemic erythroid cell lines induced by a raf- and myc-containing retrovirus differentiate in response to erythropoietin. - Klinken, S P (1988)
In vitro infection of murine fetal liver cells with a retrovirus containing v-raf and v-myc oncogenes has produced continuous lines of immature erythroid cells that are leukemogenic. These cells synthesized a factor that stimulated their growth in vitro before autonomous variants emerged. Approximately 1000 high-affinity erythropoietin receptors could be detected per cell, and the hormone induced terminal differentiation in these cells. The lines were generated at an extremely low frequency (approximately 1 in 10(7) cells), suggesting that the combination of raf and myc is insufficient to develop erythroid cell lines and that additional events are necessary for transformation.